2020
DOI: 10.1136/annrheumdis-2020-eular.1993
|View full text |Cite
|
Sign up to set email alerts
|

Sat0030 a Novel Association Between Anti-Carbamylated Antibodies and Interstitial Lung Disease in Patients With Rheumatoid Arthritis

Abstract: Background:Interstitial lung disease (ILD) is associated with a significant increase in morbidity and mortality in patients with rheumatoid arthritis (RA). Therefore, an early diagnosis is fundamental. Anti-carbamylated proteins (Anti-CarP) have been described in different chronic respiratory diseases without a previous history of RA.Objectives:The aim of this study was to analyse the association between Anti-CarP and ILD in RA patients.Methods:We performed a cross-sectional study, including RA patients fulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The remaining studies mostly reported varying degrees of association between RF and/or ACPA positivity and RA-ILD. [30][31][32][33][34][35][36][37] Most of these analyses were not adjusted for baseline factors and had low patient numbers, so the quality of evidence was considered to be low for the purposes of the current study.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…The remaining studies mostly reported varying degrees of association between RF and/or ACPA positivity and RA-ILD. [30][31][32][33][34][35][36][37] Most of these analyses were not adjusted for baseline factors and had low patient numbers, so the quality of evidence was considered to be low for the purposes of the current study.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%